Risk Taking, Limited Liability and the Competition of Bank Regulators - Hans-Werner Sinn (Center for Economic Studies and ifo Institute (CESifo), 2001)
Limited liability and asymmetric information between an investment bank and its lenders provide an incentive for a bank to undercapitalise and finance overly risky business projects. To counter this market failure, national governments have imposed solvency constraints on banks. However, these constraints may not survive in systems competition, as systems competition is likely to suffer from the same type of information asymmetry which induced the private market failure and which brought in the government in the first place (Selection Principle). As national solvency regulation creates a positive international policy externality on foreign lenders of domestic banks, there will be an undersupply of such regulation. This may explain why Asian banks were undercapitalised and took excessive risks before the banking crisis emerged.
Keywords: 330; systems competition; Basel II; banking with limited liability and Lemon bonds